Progress in female education and employment in the United Arab Emirates towards Millennium Development Goal (3) - Gender Equality - Kemp, Linzi (2013)
The purpose of this paper is to investigate the progress in the United Arab Emirates towards achievement of Millennium Development Goal (3), "gender equality", by the target date of 2015.Design/methodology/approach ‐ Demographic, social, and labor force statistics are collected from United Arab Emirates' government reports, the World Economic Forum, and UNESCO. Analysis is conducted to investigate current trends of gender equality in education and employment.Findings ‐ Results for the education of women have been at a consistently high level for some years. Two themes are found for such progress: a government strategy to increase women's access to education; societal acceptance of educated women. Gender equality in employment is slow due to three themes: study choice dictates employment potential; recruitment within a narrow range of occupations; employment more likely within public sector employment. The future of gender equality in the United Arab Emirates will continue to be more positive for women in education than for employment.Research limitations/implications ‐ A limitation is the paucity of academic study about gender equality in education and employment in the United Arab Emirates. Reliability and validity of the study is somewhat limited by unverified, non-specific, and older data on education and employment.Practical implications ‐ Improved strategies to increase study choice are required to enlarge the scope of women's careers. Management of the talent pool of educated females can increase women's share of paid employment in the future.Social implications ‐ A faster rate of change is required towards societal acceptance of women in employment to match female educational attainment.Originality/value ‐ The research is important for two reasons relevant for achievement of MDG (3) by 2015. Remarkable progress has been made on gender equality in education, and awareness is raised on limitations in the future for the employment of women.